Perceived Patient Safety Culture among Healthcare Providers in Southern Jordanian Hospitals during COVID-19 Pandemic - Asma Alamsidin; Mohammad Alyahya; Mohammad Suliman; Nihaya Al-Sheyab; Mohammed ALBashtawy (Jordan University of Science and Technology, 2023)
Background: A good and continuous assessment of the safety culture in the area of providing services in the healthcare sector will provide an initial step towards providing safe conditions for patient care. Aims: This study aimed to evaluate the perception of patient safety culture among healthcare providers in southern Jordanian hospitals during the COVID-19 pandemic. Method: A cross-sectional study was conducted among healthcare providers (physicians, nurses, and their administrators). Between July and November 2021, data was gathered by an Arabic version of the Hospital Survey of Patient Safety Culture Questionnaire (HSPSC) from 531 healthcare providers using the convenience sample approach. In four southern Jordanian hospitals.  Results: This study found that there were some areas of strength such as: organizational learning/continuous improvement, communication openness, communication about errors, supervisor, manager, or clinical support for patient safety, and hospital management support for patient safety. The reporting-related composites (response to error and reporting patient safety events), staffing, teamwork across hospital units, and information exchange were areas for improvement. Conclusion: There was a need for advancement in the practices of patient safety culture in southern Jordanian hospitals. Reporting-related composites, staffing, handoffs, and information exchange are areas of patient safety that need quick refinement.